Gluten-Free Diet Only during Pregnancy Efficiently Prevents Diabetes in NOD Mouse Offspring - Julie C. Antvorskov; Knud Josefsen; Martin Haupt-Jorgensen; Petra Fundova; David P. Funda; Karsten Buschard (Journal of Diabetes Research)
Studies have documented that the pathogenesis of autoimmune diabetes is influenced by the intake of gluten. Aims. To investigate the importance of gluten exposure during pregnancy and the subsequent development of autoimmune diabetes in offspring. Methods. Nonobese diabetic mice were divided into 7 groups to receive combinations of gluten-free and standard diet before, during, or after pregnancy. Diabetes incidence in offspring was followed in each group (n=16–27) for 310 days. Insulitis score and intestinal expression of T-cell transcription factors (RT-QPCR) were evaluated in animals from the different diet groups. Results. If mothers were fed a gluten-free diet only during pregnancy, the development of autoimmune diabetes in offspring was almost completely prevented with an incidence reduction from 62.5% in gluten-consuming mice to 8.3% (p<0.0001) in the gluten-free group. The islets of Langerhans were less infiltrated (p<0.001) and the intestinal expression of RORγt (Th17) (p<0.0001) reduced in mice whose mothers were Gluten-free during pregnancy. Conclusion. A gluten-free diet exclusively during pregnancy efficiently prevents autoimmune diabetes development in offspring and reduces insulitis and intestinal expression of RORγt (Th17).